Atrial fibrillation detection with a portable device during cardiovascular screening in primary care. Issue 16 (4th February 2020) - Diamantino, Adriana C; Nascimento, Bruno R; Beaton, Andrea Z; Nunes, Maria Carmo P; Oliveira, Kaciane K B; Rabelo, Lara C; Barbosa, Marcia M; Tompsett, Alison R; Olivieri, Laura; Mata, Mariana D; Costa, Waydder Antônio A; Pereira, Augusto F; et al.
Abstract : Introduction: A novel handheld dual-electrode stick is a portable atrial fibrillation (AF) screening device (AFSD). We evaluated AFSD performance in primary care patients referred for echocardiogram (echo). Methods: The AFSD has a light indication of irregular rhythm and single-lead ECG recording. Patients were instructed to hold the device for 1 min, and AF indication was recorded. A 12-lead ECG was performed for all AFSD-positive patients and 250 patients with negative AFSD screen. Echos were performed based on a clinical risk score: all high-risk patients and a sampling of low-risk patients underwent complete echo. Intermediate risk patients first had a screening echocardiogram, with a follow-up complete study if abnormality was suspected. Results: In 5 days, 1518 patients underwent clinical evaluation and cardiovascular risk stratification: mean age 58±16 years, 66% women. The AFSD was positive in 6.4%: 12.6% high risk, 6.1% intermediate risk and 2.2% low risk. Older age was a risk factor (9.3% vs 4.8% in those more than and less than 65 years, p=0.001). AFSD positive was independently associated with heart disease in echo (OR=3.9, 95% CI 2.1 to 7.2, p<0.001). Compared with 12-lead ECG, the AFSD had sensitivity of 90.2% (95% CI 77.0% to 97.3%) and specificity of 84.0% (95% CI 79.3% to 88.0%) for AF detection. Conclusion: AFSD demonstrated high sensitivity for AF detection in primary care patients referred for echo. AF prevalence was substantial and independently associated with structural or functional heart disease, suggesting that AFSD screening could be a useful primary care tool to stratify risk and prioritise echo.